2015
DOI: 10.1177/0022034515585125
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFII Stimulates Dentin Sialophosphoprotein Expression and Mineralization in Odontoblasts

Abstract: Chicken ovalbumin upstream promoter transcription factor 2 (COUP-TFII), an orphan nuclear receptor belonging to the steroid-thyroid hormone receptor superfamily, plays an important role in cell fate determination of various tissues. However, the specific role of COUP-TFII in tooth development has not yet been elucidated. In the present study, we aimed to explore the role of COUP-TFII in dentin sialophosphoprotein (DSPP) expression and matrix mineralization in odontoblast-lineage cells. In primary human dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…After 4 h of incubation with the siRNAs–liposome complex, the cells were changed with 2% FBS-containing media and cultured for 24 h. The cells were then treated with FGF2 with or without the indicated chemical inhibitors for 24 h. Pre-designed and validated siRNAs were used as follows: COUP-TFII Silencer Pre-designed siRNA (ID#139842, CAT# AM16708; Ambion/Thermo Fisher Scientific). The specificity and efficacy of this siRNA was validated in a previous study [ 17 ]. Knockdown of MEK2 was accomplished using two distinct non-overlapping siRNAs against MEK2, si-MEK2 #1 (AccuTarget siRNA, #1383748 Duplex; Bioneer, Daejeon, South Korea) and si-MEK2 #2 (AccuTarget siRNA, #1383749, Duplex; Bioneer).…”
Section: Methodsmentioning
confidence: 99%
“…After 4 h of incubation with the siRNAs–liposome complex, the cells were changed with 2% FBS-containing media and cultured for 24 h. The cells were then treated with FGF2 with or without the indicated chemical inhibitors for 24 h. Pre-designed and validated siRNAs were used as follows: COUP-TFII Silencer Pre-designed siRNA (ID#139842, CAT# AM16708; Ambion/Thermo Fisher Scientific). The specificity and efficacy of this siRNA was validated in a previous study [ 17 ]. Knockdown of MEK2 was accomplished using two distinct non-overlapping siRNAs against MEK2, si-MEK2 #1 (AccuTarget siRNA, #1383748 Duplex; Bioneer, Daejeon, South Korea) and si-MEK2 #2 (AccuTarget siRNA, #1383749, Duplex; Bioneer).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that dentin sialophosphoprotein (DSPP), dentin matrix protein 1 (DMP1), type 1 collagen (COL1), and alkaline phosphatase (ALP) are markers of odontoblast mineralization. 3,4 Klf10 and testicular acid phosphatase have been reported to play important roles in promoting odontoblast mineralization, [5][6][7] but the regulatory mechanism of odontoblast mineralization is still undefined. Thus, identifying factors that effectively promote odontoblast mineralization and determining the regulatory mechanism of odontoblast mineralization were major goals of this study.…”
Section: Introductionmentioning
confidence: 99%
“…We show that an evolutionarily conserved NCCE in the Nrp2 promoter supports NKX2-1/COUP-TFII interaction and reporter activation (Figure S12A, F and G). NCCE are also enriched among genes implicated in inner ear morphogenesis; in odontogenesis (which involves COUP-TFII and NKX2-3 (Han et al, 2018; Hur et al, 2015); and pancreatic beta cell fate specification (regulated by COUP-TFII and NKX2-2 (Boutant et al, 2012; Gutierrez et al, 2017; Papizan et al, 2011). In contrast, genes in which NKX and COUP-TFII sites are all separated by 30-60 bp show significantly less enrichment in NCCE-associated GO terms for morphogenesis or organogenesis, and/or are enriched in distinct embryonic and developmental processes.…”
Section: Discussionmentioning
confidence: 99%